Vegetal BM 297 ATO as a potential food grade coating material for microencapsulation of Bifidobacterium lactis Bb12 probiotic strain under supercritical conditions - Thantsha, Mapitsi Silvester (University of Pretoria, 2015)
Dissertation (MSc)--University of Pretoria, 2014.